Syncretism of Tahlilan Ritual in Islam and Consolation Worship in Protestant Christianity in the Slametan Tradition as a Reflection of Interfaith Harmony - Setiyowati, Reny; Taufiq, Thiyas Tono (IAIN Palangka Raya, 2024)
The Tradition of tahlilan in Islam and consolation worship in Protestant Christianity serve as both social and spiritual rites to pray for the deceased and provide comfort to the bereaved family. This study aims to examine the syncretism of Javanese death rituals contained in tahlilan and consolation worship from the perspectives of Islam and Protestant Christianity within the selametan tradition. The research employs a qualitative approach, utilizing primary data sources and analyzing them through Arnold Van Gennep's anthropological theory, the rites of passage. The study's findings indicate that there is syncretism between the tahlilan ritual in Islam and the worship service of consolation in Protestant Christianity within the selametan tradition. Although there are theological differences, both rituals emphasize social and humanitarian aspects, offering empathy and solidarity to the bereaved family. Tahlilan reflects the Islamic belief in the importance of prayer for the soul of the deceased, while the worship service of consolation provides spiritual support and assurance of resurrection in Christianity. This syncretism demonstrates the openness of religious rituals to adapt, creating interfaith harmony and combining religious practices with the local Javanese culture.